An Efficient Method for Making an Educational Program - Bernát, László (Acta Agraria Debreceniensis, 2003)
Distance education, a new teaching method widely-spread in higher education nowadays, requires the extent use of multimedia self-study educational programs besides the traditional means and methods. Experience shows that besides certain types of software like encyclopedias, dictionaries, language manuals etc. there is an ever growing demand for appropriate educational programs that can be tailor made, adapted or modified for various kinds of students. These programs reflect the teacher’s approach to the subject and contain the relevant, up-to-date information. Since they are used in a relatively limited circle, usually within a faculty of an institution or within a single subject area, it is crucially important to be able to produce them with as little energy and time as possible. There is a PhD research program, aiming at creating a flexible multimedia framework, that can be a possible solution to the problem. This framework can be easily filled with different teaching materials compiled by certain teachers without advanced knowledge of informatics. The framework itself is carefully designed and guarantees high quality.